PROGRAM PELATIHAN KESELAMATAN KERJA DALAM JAMINAN SOSIAL KETENAGAKERJAAN BAGI PEKERJA MEP (MEKANIKAL, ELKTRIKAL, PLUMBING DAN AC ) LOKASI SAWANGAN NUSA DUA BALI - Wiryajati, I Ketut; Yadnya, Made Sutha; Adnyani, Ida Ayu Sri; Citarsa, Ida Bagus Fery; Satiawan, Nyoman Wahyu; Suksmadana, I Made Budi (Jurnal Pepadu, 2025)
The importance of Mechanical, Electrical, Plumbing and Air Conditioning (MEP) cannot be overlooked, as these systems are interconnected to create a comfortable and safe environment. For example, without a good electrical system, mechanical devices such as air conditioners and heaters cannot function. Similarly, without adequate plumbing, the provision of clean water inside the building will inevitably be disrupted. MEP also affects the energy efficiency and operations of buildings, which ultimately impacts the comfort of its occupants. With a better understanding of MEPs, both developers and building users can ensure that each component is functioning properly. For MEP workers, each mass per group consists of 5-10 people, provided with 6 groups, so that the total number of workers is around 30 people. For this service stage, only 20 people registered and attended. The result of this service is consistency, standards, and efficiency in the operation of good building management. Keywords: Mechanical; Electrical; Plumbing; Efficiency; Energy